Rituximab treatment in myasthenia gravis - Vesperinas-Castro, Ana; Cortés-Vicente, Elena (Frontiers in Neurology, 2023)
Myasthenia gravis (MG) is a chronic autoimmune disease mediated by antibodies against post-synaptic proteins of the neuromuscular junction. Up to 10%–30% of patients are refractory to conventional treatments. For these patients, rituximab has been used off-label in the recent decades. Rituximab is a monoclonal antibody against the CD20 protein that leads to B cell depletion and to the synthesis of new antibody-secreting plasma cells. Although rituximab was created to treat B-cell lymphoma, its use has widely increased to treat autoimmune diseases. In MG, the benefit of rituximab treatment in MuSK-positive patients seems clear, but a high variability in the results of observational studies and even clinical trials has been reported for AChR-positive patients. Moreover, few evidence has been reported in seronegative MG and juvenile MG and some questions about regimen of administration or monitoring strategies, remains open. In this review, we intend to revise the available literature on this topic and resume the current evidence of effectiveness of Rituximab in MG, with special attention to results on every MG subtype, as well as the administration protocols, monitoring strategies and safety profile of the drug.